2011
DOI: 10.1177/1403494811414250
|View full text |Cite
|
Sign up to set email alerts
|

Lack of support structures in prioritization decision making concerning patients and resources. Interviews with Swedish physicians

Abstract: Aim: To investigate physicians’ experiences in relation to prioritization and financing in health care in order to gain a deeper understanding of the reasons behind their standpoints. Methods: Eighteen physicians, seven women and eleven men, aged 30 to 69 years were interviewed and the text was analyzed using an inductive approach, also described as conventional qualitative content analysis. Results: Experience of setting healthcare priorities and difficult decision making differed widely among the physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…18 Further studies have reported that physicians expressed a lack of support structures 19 and a lack of basic training and support of ethical principles. 15 There was a need for more open dialogues and discussions about priority setting, more practical and clearer national guidelines, 15,19 as well as more evidence for the treatment of elderly multimorbid patients. 20 Although Sweden has developed a sophisticated approach to priority setting in healthcare, there is thus still a need for a more detailed insight on how it permeates the micro level of decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Further studies have reported that physicians expressed a lack of support structures 19 and a lack of basic training and support of ethical principles. 15 There was a need for more open dialogues and discussions about priority setting, more practical and clearer national guidelines, 15,19 as well as more evidence for the treatment of elderly multimorbid patients. 20 Although Sweden has developed a sophisticated approach to priority setting in healthcare, there is thus still a need for a more detailed insight on how it permeates the micro level of decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…17 In 2015, it was reported that 76% of the heads of different hospital departments applied the NBHW’s national guidelines, 33% in their original form, 69% through local guidelines. 18 Further studies have reported that physicians expressed a lack of support structures 19 and a lack of basic training and support of ethical principles. 15 There was a need for more open dialogues and discussions about priority setting, more practical and clearer national guidelines, 15 , 19 as well as more evidence for the treatment of elderly multimorbid patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation